Innovation of Tepache Probiotic Drink Made from Apple Skin (Malus Domestica) - Rosa, Adelia; Royani, Agnes Elva; Amalia, Rosela; Putri, Seprianti Randika; Aini, Kurratul (Program Studi Pendidikan Biologi, 2024)
The beverage industry currently continues to innovate to create unique and sustainable products. One interesting innovation is the development of the Tepache drink made from apple peel. Tepache is a traditional fermented drink from Mexico which is usually made from pineapple skin. However, in this innovation, apple skins are used as the main raw material to create tepache drinks which are rich in nutrients and environmentally friendly. The process of producing Tepache drinks from apple skins involves fermenting apple skins with sugar and natural yeast. During fermentation, microorganisms such as yeast and lactic acid bacteria convert sugars into organic acids, resulting in a refreshing slightly sour taste. Apple skin is rich in fiber, antioxidants, and phenolic compounds that provide additional health benefits to this drink. This innovation not only creates attractive beverage products, but also contributes to efforts to reduce apple peel waste which is often wasted. The use of apple peel as a raw material for Tepache drinks is a sustainable step in the beverage industry, as well as offering a healthy and environmentally friendly alternative drink.